Hirarki Tujuan Pembelajaran Implikasi Teoretis Dalam Pembelajaran Di Madrasah Ibtidaiyah Dan Sekolah Dasar - Putri, Inshita Arisna; Maulana, Aldi; Rizqi, Mohammad Azrir; Afroni, Akhmad (Al-Riwayah : Jurnal Kependidikan, 2025)
This research discusses the order of learning objectives at the Madrasah Ibtidaiyah level using a qualitative method. The article explains the types of learning goals, including national, institutional, curricular, and instructional objectives. Each level plays an important role in supporting the success of the learning process. Understanding how to structure these objectives helps teachers in planning their lessons more effectively. It also makes it easier to design learning strategies and evaluate student outcomes. Therefore, organizing learning goals properly is a crucial part of effective teaching and learning in Islamic elementary schools.